The Nrf2 transcription factor contributes both to the basal expression of glutathione S-transferases in mouse liver and to their induction by the chemopreventive synthetic antioxidants, butylated hydroxyanisole and ethoxyquin. (February 2000) - Hayes, J. D.; Chanas, S. A.; Henderson, C.J.; McMahon, M.; Sun, C.; Moffat, G.J.; Wolf, C. R.; Yamamoto, M.
Abstract : An overview is provided of the cancer chemo-prevention actions of phenolic antioxidants and 6-ethoxy-1, 2-dihydro-2, 2, 4-trimethylquinoline (ethoxyquin). These agents principally appear to exert their beneficial effects through induction of phase II drug-metabolizing enzymes such as glutathione S-transferase (GST). The requirement for oxidative metabolism of the synthetic antioxidants to carbonyl-containing compounds, including quinones, in order that they can induce gene expression is discussed. Previous work has shown that the basic leucine zipper transcription factor Nrf2 is involved in induction of GST by the phenolic antioxidant butylated hydroxyanisole (BHA). Evidence is provided from a mouse possessing a targeted disruption of the Nrf2 gene that, in murine liver, the transcription factor regulates basal expression of several class Alpha and class Mu GST subunits, but not class Pi GST. In the Nrf2 knock-out mouse, hepatic induction of class Alpha and class Mu GST by BHA and the synthetic antioxidant ethoxyquin is similarly impaired, suggesting that these agents affect gene activation by a related mechanism. Significantly, residual induction of GST by antioxidants is apparent in the Nrf2 mutant mouse, indicating the existence of an alternative mechanism of gene activation.